Pentingnya Pendidikan Moral bagi Remaja di Era Digital untuk Interaksi yang Positif di Masyarakat - Trisna, Nila; Muharrir, Muharrir; Moulia, Nouvan; Jalaluddin, Jalaluddin; Zulfikar, Muhammad Nahyan; Yuana, Adella; Munandar, Agung (Lok Seva: Journal of Contemporary Community Service, 2025)
This community service activity was held on Sunday, November 26, 2023, at SOS Children’s Village Meulaboh by the Faculty Team of the Law Department, Universitas Teuku Umar. The purpose was to provide adolescents with an understanding of the importance of moral education in the digital era. The material covered basic moral concepts, the positive and negative impacts of technology on adolescent behavior, and the urgency of digital ethics in daily life. The results showed that most participants had not fully understood the impact of technology on morality, especially regarding cyberbullying, addiction, and the decline of direct social interaction. In fact, moral behavior is essential not only in digital spaces but also as a foundation for healthy relationships in society. On the other hand, technology also provides positive opportunities for accessing information, self-expression, and expanding social connections. Therefore, contextual moral education is key to shaping digitally literate, ethical, and socially responsible youth. This activity is expected to be a starting point for raising awareness and encouraging adolescents to apply moral values in their daily lives, both online and offline. Thus, the younger generation can grow into individuals who are morally grounded and digitally competent.